Effects of growth factors and cytokins on soft tissue regeneration in patients with diabetes mellitus - Ekaterina Leonidovna Zaytseva (Endocrinology Research Centre, 2014)
Delayed wound healing is characteristic of a glycemic disorder and often results in trophic ulcer formation, ? a process still poorly understood but likely multifaceted. Current review addresses latest reports from cellular and molecular studies of soft tissue regeneration in patients with diabetes mellitus.